The Effect of Substitution of Snakehead Fish and Purple Eggplant Flour on The Acceptability of Biscuits for Stunting Prevention - Misnati, Misnati; Pomalingo, Anna .Y; Ranti, Irza Nanda; Nuryani, Nuryani (Universitas Airlangga, 2023)
The development of supplementary food formulas for toddlers made from local foods can be an alternative in handling child nutritional problems. Purpose of study was to observe the acceptability of biscuits substitution of snakehead fish meal and purple eggplant flour. Design of study was an quasi experimental using postest only control group design with four treatments namely substitution of snakehead fish meal and purple eggplant flour. The ratio of wheat flour, fish meal and purple eggplant flour is 100%: 0 : 0,85% : 10% : 5%, 70% : 20% : 10%, and 55% : 30% : 15%. The results of the study based in the color characteristic the highest score after control was F1 (score = 2.47), the taste aspect F1 (score = 2.7), the aroma aspect F1 (score = 2.41), thetexture/crunch F1 (score = 2.65). There was an effect of substitution of snakehead fish meal and purple eggplant flour on color acceptability (p = 0.000) and taste (p = 0.003), there is no effect of substitution of snakehead fish meal and purple eggplant flour on aroma receptivity (p = 0.306) and crispness (p = 0.155). In conclusion, there are significant differences in the color and taste characteristics of cookies substitution of snakehead fish flour and purple eggplant flour between F0, F1, F2 and F3.